COMPARISON OF RECURRENCE OF URETHRAL STRICTURE AFTER INTERNAL OPTICAL URETHROTOMY WITH AND WITHOUT POST-OPERATIVE ORAL STEROIDS IN DISTRICT DERA ISMAIL KHAN - ILYAS, M; SEERWAN, M; ADNAN, M; NASEEM, A; JAVED, N; HUSSAIN, M (Biological and Clinical Sciences Research Journal, 2023)
Urethral stricture is one of the most common diseases in urology. The urethral structure is the narrowing of the urethral lumen due to spongiofibrosis. It is notorious for its recurrence and accounts for the major burden on the Urology department. Internal optical urethrotomy is considered the first line of treatment for urethral stricture. When combined with clean intermittent self-catheterization, and Intralesional injections, better results could be obtained. This study compares the recurrence of urethral stricture after internal optical urethrotomy with and without post-operative oral steroids in the population of Dera Ismail Khan. The study was a non-randomized control trial done in the Urology Department, DHQ/MTI-TH, Dera Ismail Khan, Pakistan, from January 2021 to June 2021. The patients from the urology outdoor and emergency of DHQ Teaching Hospital were included in the study. A total of 152 patients were divided by lottery method into two groups’ an experimental group and Control group, each containing 76 patients. After losing follow-up, the remaining patients who completed the study were 128. The patients in both groups underwent internal optical urethrotomy with a cold knife. The experimental group of patients received oral steroids for 4 weeks. The control group didn’t receive steroids after the procedure. The mean age in the experimental group was 41 ± 09 years, while in the control group, it was 36 ± 13 years. After 6 months, the recurrence was observed in 12 patients (18.75%) in the experimental group and 25 in the control group (39.06%). These results showed a statistically significant difference in recurrence rate between these two groups with a p-value of 0.0123. Based on the results, it can be concluded that the use of oral steroids after internal optical urethrotomy decreases the risk of recurrence of urethral stricture significantly.